Normal findings in CT and MRI - Möller, Torsten B; Reif, Emil (Georg Thieme, 2000)
The key for any beginning radiologist who wishes to recognize pathological findings is to first acquire an ability to distinguish them from normal ones. This outstanding guide gives beginning radiologists the tools they need to systematically approach and recognize normal MR and CT images.
Keywords: radiologie; Magnetic Resonance Imaging; magnetická rezonanční tomografie; radiologie, nukleární medicína a zobrazovací metody; Radiology; Tomography, X-Ray Computed; počítačová rentgenová tomografie